Concept Paper on The Efficacies and Twist of Human Resource Management future with the New Era of Coronavirus Pandemic (Covid-19) for Organisational and Institutional Action - Adam, Abdul-Kahar; Manu, Isaac Yaw (International Journal of Business, Management and Economics, 2021)
The essence of this paper is eminent to advance the study of Human Resource Management (HRM) in the profound new directions that has been introduced due to the covid-19 pandemic. This particular review elaborates on the following such as: Challenges Caused by Covid-19 to HRM Principles and Practice, HRM Outlook within Continents in this Coronavirus Pandemic, How Information Technology can still grow HRM in new Practices, The Case of HRM Practice in Developing World with Covid-19, How Both National and International HRM Practice is portrayed with Covid-19, Moving Forward with HRM Practice and Covid-19, and Organisational and Institutional Challenges and Demands in HRM Policies and Law. The general conclusion with this new Human Resource Management is associated with massive application of technology that Human Resource Management practices in various organisational operations and ways of doing things in the traditional HRM way has changed. Many of the roles are been performed remotely using internet and relevant HRM laws, applications and policies to deliver in managing work and the people. This is eminent for HRM practitioners and professionals to further educate and train themselves in this covid-19 era to avert themselves with the new principles instituted by organisations and governments in the area of HRM of activities and people. In this review the HRM is been twisted and thereby its efficacies are challenged which is why this new study is important to the practitioners and professionals to adapt and/or adopt.